Silica dissolution and its inhibition with quartz sand: Static model approach - Elraies, K.A. (2013)
Silica scale is one of the critical limiting factors that affect production wells during chemical flooding. Silica deposition is mainly caused as a result of silica dissolution and its polymerization and coprecipitation with other minerals present in reservoir brine. The solubility of silicate is complicated by its dependence on multi factors including pH, silica concentration and brine salinity. In this paper, series of experiments were performed to investigate the effect of pH and brine salinity on silica dissolution or solubility. Static bottle experiments incorporating quartz sand were used to study silica dissolution in the presence and absence of scale inhibitor. The sand mineralogy and silica content were measured using X-RAY diffraction (XRD) and X-RAY Fluorescence (XRF) respectively. X-RAY Fluorescence indicated that the original concentration of silica on the quartz sand was 94.4. Further results showed that the silica dissolution increased significantly with the increase in the brine salinity. The maximum silica dissolution was observed with the highest brine salinity of 60,000 ppm which corresponds to 6.45 of the total silica present in the sample. This is also attributed to the pH of the brine in which the lowest pH was achieved with the highest brine salinity of 60,000 ppm. However, 77 of the soluble silica was inhibited when 250 ppm of Ploy Acrylic Acid was introduced to 60,000 ppm brine solution. This study demonstrated that the brine salinity has a dramatic impact on silica dissolution particularly during chemical flooding where salinity and pH changes continuously as the chemical slug flows in the reservoir. Â© (2013) by the Society of Petroleum Engineers.